Answer:
(3,1)
Explanation:
5x + 3y = 18
2x + 3y = 9
So we can use elimination here to solve this system of equations by multiplying the second equation by -1
Now we have:
5x + 3y = 18
-2x - 3y = -9
Now we add straight down and combine like terms
The y terms cancel and we are left with 3x = 9, dividing both side by 3 we get x = 3
Now we can plug this x value into one of the original equations to solve for our y value
I will use the first equation: 5(3) + 3y = 18 → condensing the terms we get 15 + 3y = 18 → subtracting the 15 from both sides we get 3y = 3 → dividing both sides by 3 we get y = 1
The solution to this system of equations is (3, 1)